Pengaruh modal kerja terhadap profitabilitas pada PT. hutama karya - Suliswati; Wulandari; Aliah Pratiwi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The purpose of this study is to determine and analyze the effect of working capital on profitability at PT. Hutama Karya. This study uses associative research using quantitative data from secondary data sources. The instrument is in the form of financial reports from 2014 to 2023 consisting of a list of tables containing data on current assets, current liabilities, net income and total assets. The population in this study is all financial reports of PT. Hutama Karya from 1961 to 2023, which is 63 years. The sample in this study is the financial report of PT. Hutama Karya for 10 years, namely from 2019 to 2023. The sampling technique used in this study is purposive sampling. The data collection technique used is documentation and literature study and uses simple linear regression data analysis, correlation coefficients, determination tests and t-tests. The results of the study indicate that Net Working Capital (NWC) has no effect on Return On Assets (ROA) of PT. Hutama Karya with Net Working Capital (NWC) contribution to Return On Asset (ROA) is 4.7%.